Great powers : America and the world after Bush - Barnett, Thomas P. M. (New York G.P. Putnam's Sons, 2009)
The Bush administration did much to disconnect or alienate America from the world. Now, with a chance to start over, what do we do? Where's the world going, and how do we become a leader again in the most profound reordering since the end of World War II? The "great powers" are no longer just the world's major nation-states, but powerful forces moving with us and past us. Here, strategist Barnett offers an analysis of the grand realignments already here or coming up fast in economics, diplomacy, defense, technology, security, the environment, and much more. The opportunities they present are far greater than the perils, and Barnett gives us a fundamental understanding of both. Many say America is in decline, and we just have to deal with it. Barnett says no: Globalization as it exists today was built by America--and it's time for America to shape and redefine what comes next.--From publisher description
Keywords: EEUU -- Relaciones exteriores -- Siglo 20o